Back Cover: Diets Containing Egg or Whey Protein and Inulin Fiber Improve Energy Balance and Modulate Gut Microbiota in Exercising Obese Rats. Issue 7 (3rd April 2022) - Avirineni, Bharath S.; Singh, Arashdeep; Zapata, Rizaldy C.; Stevens, Richard D.; Phillips, Caleb D.; Chelikani, Prasanth K.
Abstract : Mol. Nutr. Food Res . 2022, 66, 202100653 DOI: 10.1002/mnfr.202100653 High protein diets containing egg or whey protein, together with inulin fiber and exercise, improved energy balance in obese rats by decreasing food intake partly through the gut hormone cholecystokinin, enhancing energy expenditure, and decreasing fat mass. Interestingly, the diet and exercise interventions improved glycemic control, modulated gut microbiota composition and function, and altered select circulating metabolites. This is reported by Prasanth Chelikani and co‐workers in article number 2100653 .